Anesthesiology : a comprehensive review for the written boards and recertification - Matthes, Kai; Urman, Richard D.; Ehrenfeld, Jesse M. ([New York] : Oxford University Press, 2013)
This resource contains more than 1000 updated, realistic multiple-choice questions tailored to the question content of recent American Board of Anesthesiology (ABA) exams. Key messages are repeated and highlighted in the bullets, and while focusing on most-frequently tested keywords by the ABA, it also covers new, emerging topics, such as patient safety, statistics, and ethics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Aug 12, 2013).
Keywords: Anesthesiology -- Examinations, questions, etc